Ecosystem diversity of mosquitoes (Diptera: Culicidae) in a remnant of Atlantic Forest, Rio de Janeiro state, Brazil. Issue 1 (15th November 2020) - Alencar, Jeronimo; de Mello, Cecilia Ferreira; Rodríguez‐Planes, Lucía; dos Santos Silva, Júlia; Gil‐Santana, Hélcio Reinaldo; Bastos, Amanda Queiroz; Albuquerque, Hermano Gomes; Rodrigues, William Costa; Guimarães, Anthony Érico
Abstract: Understanding mosquito biodiversity in the Atlantic Forest is important for assessing changes in the distribution of mosquito populations, which have been considered predominantly to be sylvatic. An observational study of Culicidae was conducted in a remnant of the Atlantic Forest in the Poço das Antas Biological Reserve, Silva Jardim municipality, Rio de Janeiro state, Brazil, to evaluate species diversity and the influence of climatic factors (temperature, relative humidity and rainfall) on species distribution. Two types of light trap were used: an automatic CDC trap baited with CO2 and a Shannon trap. Collections were also made using a manual suction tube. Overall, 15 700 Culicidae specimens were collected belonging to two subfamilies, 12 genera and 41 species. The most common species were Coquillettidia chrysonotum, Mansonia titillans and Coquillettidia venezuelensis . Principal component analyses indicated a major association between sampling site six and the species Anopheles albitarsis, Mansonia titilllans, Cq. chrysonotum and Cq. venezuelensis . Furthermore, diversity indices indicated that sampling sites 1, 6 and 4 displayed higher diversity and a more uniform species abundance. Culicidae abundance was positively correlated with temperature. Landscape units exhibited contrasting community compositions of mosquitoes at multiple scales, with the community composition more similar in sites with similar landscape parameters. The importance of constant entomological monitoring is underscored by the diversity of mosquito species in this reserve and their potential role in the transmission of pathogens, combined with intermittent flow of visitors to the area.